Analysis of Readiness for the Implementation of Electronic Outpatient Medical Records at Mitra Siaga Hospital, Tegal Using the DOQ-IT Approach - Dhea Farah Andiani; Danu Tirta Nadi (Proceedings Series on Health & Medical Sciences, 2026)
Electronic Medical Records (EMR) are a component of the hospital management information system (SIMRS) that is currently being developed. The complexity of the challenges in implementing EMRs necessitates a readiness assessment before they are fully implemented. This is an important step to help identify procedures, levels of importance, and to accommodate the formation of operational functions that support the optimization of EMR implementation. One of the methods that can be used to analyze the readiness for implementing information systems based on EMRs is the Doctor’s Office Quality-Information Technology (DOQ-IT) method. The implementation of EMRs at Mitra Siaga Hospital in Tegal began in April 2024, but it has not yet been fully executed. This study aims to determine the readiness for implementing outpatient EMRs at Mitra Siaga Hospital Tegal using the DOQ-IT approach. This is a descriptive quantitative study with 32 subjects, consisting of IT staff, medical record officers, doctors, and nurses. The results of the study indicate that the readiness for implementing outpatient EMRs at Mitra Siaga Hospital Tegal using the DOQ-IT approach falls into the "very ready" category. Based on the research findings, it is recommended that Mitra Siaga Hospital Tegal continue to monitor, evaluate, and periodically review the implementation of EMRs, as there may still be challenges or obstacles during the implementation process.